The beetle family Carabidae of Costa Rica: The genera of the Cryptobatida group of subtribe Agrina, tribe Lebiini, with new species and notes on their way of life (Insecta: Coleoptera) - Erwin, Terry L. (Zootaxa, 2004)
Eight genera and eighteen species of the Cryptobatida group of subtribe Agrina, Lebiini, living in Costa Rica are diagnosed, described, illustrated or referenced and new species assigned to inclusive genera. Occurrences of some taxa outside of Costa Rica are also reported, these ranging from Texas to Argentina. Subtribe Agrina consists of those species formerly included in the Subtribe Calleidina. Four new species of Aspasiola Chaudoir 1877 are described: A. bonita Erwin, n. sp. (COSTA RICA. PUNTARENAS, Peninsula de Osa, P.N. Corcovado, Estaci n Sirena, 0 100 m, 08 28’ 0 N, 083 35’ 0 W, LS270500, 508300), A. osa Erwin, n. sp. (COSTA RICA. PUNTARENAS, Peninsula de Osa, P.N. Corcovado, Estaci n Sirena, upper Ollas Trail, 30 150 m, 08 29’ 00 N, 083 34’ 39 W), A. selva Erwin, n. sp. (COSTA RICA. HEREDIA, Estaci n Biol gica La Selva, 3.0 km S Puerto Viejo, Finca La Selva, 50 150 m, 10 25’ 55 N, 084 00’ 32 W, LN535500, 268000), A. steineri Erwin n. sp. (COSTA RICA. HEREDIA, Estaci n Biol gica La Selva, 3.0 km S Puerto Viejo, Finca La Selva, 50 150 m, 10 25’ 55 N, 084 00’ 32 W, LN535500, 268000). Two new species of Hyboptera Chaudoir 1872 are described: H. apollonia Erwin n. sp. (PANAM , COL N, Porto Bello, 113 m, 09 33’ 0 N, 079 39’ 0 W), H. auxiliadora Erwin n. sp. (USA. TEXAS, Hidalgo County, Mission; Bentsen State Park, 26 10’ 22" N, 098 22’ 56" W). Alkestis Liebke 1939 is a nomen dubium and possible junior synonym of Lelis Chaudoir 1869. Aspasiola rutilans ignea Bates 1883 is changed to full species, Aspasiola ignea Bates new status. Pseudolebia Basilewsky 1942 is NOT a synonym of Onota Chaudoir 1872. Pseudometabletus Liebke 1930 is a junior synonym of Cylindronotum Putzeys 1846. Pseudotoglossa rufitarsis nigrescens Mateu 1961:177 is a junior synonym of Pseudotoglossa terminalis (Chaudoir). An identification key is provided to the genera of the Cryptobatida Group and additional keys are provided for those genera with more than one species occurring in Costa Rica. Distribution data is provided for all species including their known occurrence outside of Costa Rica in adjacent Panam and Nicaragua, and other countries. Adults of species of Aspasiola, Cryptobatis, Otoglossa and Hyboptera are known to occur on shelf fungi on rotting logs and have also been fogged from the canopy of tropical trees (which probably contained shelf fungi on dead branches); adults of species of Cylindronotum, Onota, Pseudotoglossa, Valeriaaschero have also been fogged from the canopy of tropical trees and likely adults of Onota and Pseudotoglossa collected from rotten logs were associated with fungi.